The Incarcerated Parent: Examining Mother-Child Conflict at the Margins through a Bio-Ecological Lens. Issue 3 (3rd July 2019) - Rudd, Jill E.; Neuendorf, Kimberly A.; Atkin, David J.; Romano, Alicia; Gross, Clare; Ray, George
ABSTRACT: This study examined conflict, parenting communication style, and attitudes regarding the parent-child relationship for a marginalized special population: incarcerated mothers and their children. Bronfenbrenner's bio-ecological perspective served as a guiding framework, based on its ability to consider family interactions across ecological contexts, both proximal and distal to the developing child's home setting. Fifty incarcerated mothers in the central U.S. provided in-depth interviews and individual self-report surveys. Findings indicate that incarcerated mothers most frequently used an authoritative parenting communication style in conflict situations that ended positively, and authoritarian style in conflict that ended negatively. Authoritative parenting was associated with incarcerated mothers' reports of greater satisfaction with parenting. Study findings suggest that parenting communication style can help support efforts to reduce recidivism. Contextualizing these findings within Bronfenbrenner's model, the present study affirms the role of proximal as well as distal factors governing relational communication between incarcerated mothers and their children.